2018
DOI: 10.21037/tp.2018.09.13
|View full text |Cite
|
Sign up to set email alerts
|

Disease prevention & health promotion: what’s critical care got to do with it?

Abstract: Health systems are increasingly investing in efforts to prevent disease and promote health for populations. By and large, these prevention-related interventions have not been inclusive of critical care and the intensive care unit (ICU). However, we suggest that there is value-to patients, families, health systems, and society at large-in extending this continuum into the ICU setting and including the ICU in disease prevention and health promotion efforts. Including the ICU in this continuum allows the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…We suggest that taking a neighborhood-level view of povertyrelated health disparities, as some authors have done, may support both public health-and health system-based approaches to pattern recognition and preventive strategies aimed at disparity reduction. 1,[30][31][32][33][34][35][36][37] We also agree with authors who argue that worse health outcomes seen in higher-poverty neighborhoods represent more than just the aggregate of individual health risks, behaviors, and disparities. [38][39][40] Delineating the complex, intersectional relationships between individual demographic variables; patient and family health risk factors, assets, and exposures; health infrastructure of communities; and cultural and community health norms and practices offers a broader and more nuanced understanding of health inequity and the roots of disparities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We suggest that taking a neighborhood-level view of povertyrelated health disparities, as some authors have done, may support both public health-and health system-based approaches to pattern recognition and preventive strategies aimed at disparity reduction. 1,[30][31][32][33][34][35][36][37] We also agree with authors who argue that worse health outcomes seen in higher-poverty neighborhoods represent more than just the aggregate of individual health risks, behaviors, and disparities. [38][39][40] Delineating the complex, intersectional relationships between individual demographic variables; patient and family health risk factors, assets, and exposures; health infrastructure of communities; and cultural and community health norms and practices offers a broader and more nuanced understanding of health inequity and the roots of disparities.…”
Section: Discussionsupporting
confidence: 81%
“…Mechanisms by which a physical and social environment may influence need for pediatric intensive care become apparent when examining features common in high-poverty, racially segregated neighborhoods. 5,6,16,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Higherpoverty neighborhoods may lack health care infrastructure equivalent to that found in lower-poverty neighborhoods (eg, fewer or more distant points of care access or a limited number of providers who accept public insurance). 46,47 Physical living conditions and a more distressed social environment likely also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, most studies have focused on the pathological study of metabolic disease, while only a few have been carried out on the prevention of metabolic diseases [ 55 , 56 ]. Previously, Ma and coworkers have reported that lncRNAs may regulate diverse gene expressions, which are roughly summarized to epigenetic, transcriptional, and posttranscriptional levels in cardiovascular diseases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As early as in 1986, the Ottawa Charter of health promotion suggested a reorienting from the predominance of a biomedical perspective within hospitals to increasingly move in a health promotion direction (Iriarte-Roteta, 2020). Nevertheless, the health promotive perspective in ICU care (Riley, 2018) and nursing practice is still sparse (Iriarte-Roteta, 2020). Therefore, Haugdahl et al (2021) call for the ABCDEF bundle's missing 'G', entailing the identification and utilisation of salutogenic resources in long-term ICU care.…”
Section: Introductionmentioning
confidence: 99%
“…The field of intensive care has directed the negative effects that ICU stays can have (Riley, 2018). The focus largely preventing mortality is over the last decade widened to also include the prevention of secondary harm due to intensive care (Riley 2018). Correspondingly, the ABCDEF bundle is well accepted internationally.…”
Section: Introductionmentioning
confidence: 99%